On-line integration of PCR and cycle sequencing in capillaries: from human genomic DNA directly to called bases - Hashimoto, Masahiko (Oxford University Press, 2003)
A fully integrated system has been developed for genetic analysis based on direct sequencing of polymerase chain reaction (PCR) products. The instrument is based on a serially connected fused-silica capillary assembly. The technique involves the use of microreactors for small-volume PCR and for dye-terminator cycle-sequencing reaction, purification of the sequencing fragments, and separation of the purified DNA ladder. Four modifications to the normal PCR protocol allow the elimination of post-reaction purification. The use of capillaries as reaction vessels significantly reduced the required reaction time. True reduction in reagent cost is achieved by a novel sample preparation procedure where nanoliter volumes of templates and sequencing reaction reagent are mixed using a micro- syringe pump. The remaining stock solution of sequencing reaction reagent can be reused without contamination. The performance of the whole system is demonstrated by one-step sequencing of a specific 257-bp region in human chromosome DNA. Base calling for the smaller fragments is limited only by the resolving power of the gel. The system is simple, reliable and fast. The entire process from PCR to DNA separation is completed in ∼4 h. Feasibilities for development of a fully automated sequencing system in the high-throughput format and future adaptation of this concept to a microchip are discussed.